Corporate human rights performance and moral power: A study of retail MNCs' supply chains in Bangladesh. (January 2021) - Islam, Muhammad Azizul; Deegan, Craig; Haque, Shamima
Highlights: MNCs' human rights disclosures do not remain unchallenged by NGOs in Bangladesh. With greater inequity, suppliers' and MNCs' exercises of moral power become tenuous. A social audit can be exploited to give a moral dimension to economic gains. MNCs' neoliberal discourse of 'doing good only for profit' is problematic. Rana Plaza disaster is a solid example of MNCs' disintegration of moral power. Abstract: This paper investigates how particular stakeholder groups, such as labor rights non-governmental organizations (NGOs), question and even challenge the moral power of multinational companies (MNCs) to maintain human rights in their supply chains in Bangladesh. Around the time of two major factory disasters in Bangladesh (the Tarzeen fire and the Rana Plaza collapse in 2012 and 2013, respectively) we conducted a series of interviews (between 2012 and 2014) and reviewed articles in news media and NGO documents to understand how labor rights NGOs' narratives challenge MNCs and their suppliers' actual human rights performance and associated moral power within clothing supply chains. The findings show that MNCs' and their suppliers' workplace human rights performance in Bangladesh, as perceived by labor rights NGOs, is inconsistent with MNCs' public disclosures on human rights. The NGOs' counter-narratives testify to MNCs' and their suppliers' abuses of human rights and the associated moral deficit. This study draws on the notion of moral power in line with Aristotle's view of the moral actor and adds to Mehta and Winship (2010) three essential aspects of moral power – moral intention, moral capability and moral standing – by providing a new insight that suggests that MNCs and their suppliers in the developing nation context of Bangladesh lack the moral intention, moral capability and moral standing to uphold workplace human rights. We note that gaining these richer insights are possible because we directly solicit the views of NGOs and social movement organizations. The paper fills a research gap by looking at whether the adoption of the language of human rights obligations by MNCs creates any change in their moral power and human rights performance, as perceived by workers' rights NGOs.